Neurofeedback in fibromyalgia for the treatment of depression and anxiety - Barbosa Torres, Carlos; Cubo Delgado, Sixto; Bermejo García, María Luisa; Vicente Castro, Florencio (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2020)
In the present work we found a study on neurofeedback in patients with fibromyalgia syndrome. This syndrome brings together a large number of very diverse symptoms, ranging from chronic pain, chronic fatigue to sleep problems. Although it is an idiopathic syndrome, multiple studies suggest that its origin is related to the Central Sensitization Syndrome (SSC). We conducted a training through neurofeedback whose purpose is to improve the variables anxiety and depression. We use a standardized protocol of sensorimotor rhythms (SMR) that can improve the stability of the cerebral cortex, the training of these waves affect the dopaminergic system which in turn is related to the facilitation of positive emotions. The results show that neurofeedback improves significantly depression and anxiety disorders.